Khazanah Penafsiran Fiqih Hanafi: Studi Kritis terhadap Kitab Tafsir Al-Jassash - Rifhan, Muhamad Rifhan Hais; M. Afif Wafiudin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Al-Jassas is one of the prominent scholars of Quranic exegesis within the Hanafi school of thought, whose work, Ahkam al-Qur'an, serves as a primary reference in legal-oriented tafsir studies. This research aims to analyze Al-Dhahabi's critique of Ahkam al-Qur'an, which includes accusations of legal deviations, Hanafi sectarian bias, Mu'tazilite tendencies, and hostility toward Muawiyah. Through a library research approach and critical analysis, the study finds that some of Al-Dhahabi's criticisms, such as the claim of sectarian bias, are well-founded. However, the accusation of legal deviations can instead be seen as a form of interpretative improvisation that remains aligned with the principles of the Hanafi school. In conclusion, despite some valid criticisms, this work remains a monumental and authoritative contribution among Hanafi scholars.